Improving the efficiency and reliability of Cone Laying and Collecting (C2L) machine using TRIZ method - Zainal Abidin, Muhammad Reza (2024)
PLUS Berhad (PLUS) executes the temporary signing procedure when maintenance or repair works needs to be done along the highway. Setting up cones around the work area would inform incoming traffic of the lane closure, thus helping the drivers to steer into open lanes. Manually handling the cones impacts the health of the workers while also exposes the workers to the potential of being hit by live traffic and other safety hazards as well. The Cone Laying and Collecting (C2L) semi-automated machine was then developed to address the health and safety issues faced by the workers. The machine’s features enable it to lay and collect cones as per PLUS requirements. However, the machine has not yet been tested on its reliability and operational efficiency when under actual working condition, which is a crucial requirement for it to replace the manual cone handling procedure. In this thesis, the C2L machine was tested under several parameters. During the laboratory test, the C2L machine was tested on a test rig to determine the impact of road surface condition on the machine’s operation. The operational efficiency of the machine and the mechanical failures that occurred during the test were analysed. TRIZ methodologies were then used on redesigning the machine to address the mechanical failures and further improve the machine’s efficiency and reliability. The improved C2L machine was then tested under the field test to determine if it can lay and collect cones according to PLUS requirement. The result from the Laboratory Test showed that the operational efficiency of the C2L machine was consistent on both smooth (Test Motion A) and uneven surface (Test Motion B), suggesting that the efficiency of the C2L machine is not impacted by the road condition. For Test Motion A, the mean of the Total distance traveled on the test rig per minute was 9.43 (m/min), while the median was 9.81 (m/min). For Test Motion B, the mean was 9.54 (m/min), and the median was 10.34 (m/min). Next, the mean of the Total actual distance travelled per minute under Test Motion A was 77.25 (m/min) while the median was 81.63 (m/min). The mean under Test Motion B was 76.17 (m/min) while the median was 82.59 (m/min). The third operational data that was analysed was the Total laying and collecting movements per minute. For Test Motion A, the mean was 7.73 (count/min) while the median was 8.13 (count/min). For Test Motion B, the mean was 7.62 (count/min) while the median was 8.26 (count/min). In terms of reliability analysis, three failed components were redesigned using TRIZ methodologies. The welded joint had a high MTTR (1:00:00), as did the hook spring (1:50:00), while the PLC had low MTTF (0:10:12) and MTBF (0:12:16). These results indicate that these three components may severely affect the reliability of the C2L machine. The redesigned C2L 02 machine was then tested under several Field Test parameters. Overall, the results showed that the machine could lay and collect cones as per PLUS requirements. The time to lay and collect 10 sets of safety cones and 10 sets of super cones during Field Test 1 was consistently 5 minutes across two days. For Field Test 2, the time lay and collect 20 sets of cones in a straight and tapered orientation remained at 10 minutes on both days. These positive results suggested that the C2L 02 machine is reliable and operationally efficient to execute the cone laying and cone collecting activities along PLUS highway. It enhances safety and efficiency in highway maintenance by reducing worker risks and physical strain, leading to fewer injuries and better operational continuity.